Aporte de los sistemas multimedia y redes sociales en los emprendimientos de las pymes de Babahoyo - Campi Maldonado, Elvis Alberto (2019)
Small and medium-sized SMEs contribute directly to the local and national economy, since they are creative sources of employment, employing a large part of the economically active population, due to this it is the importance of their permanence and for this reason they must be supported to provide an economical but effective method to carry out mass advertising and in this way their products and services can be made known to their current and future potential customers. Thus also contribute to the generation of communication and fidelity links, in order to improve its services and services of attention and sales to its customers. The use of social networks is presented as an alternative to the communication process for companies, which is economical and very effective for SMEs to receive them as a means of communication with their customers and suppliers, as well as publicize the goods and services that They offer to the market. Another reason for the use is that the contents can be updated periodically and immediately without major complications. Based on the above, in this case study reference is made to the competitive advantages in which they can support SMEs in the city of Babahoyo, there are also some examples of SMEs that have an active presence within social networks and what have been its advantages and disadvantages of using them as a means of communication and promotion